Keeping together: Which factors characterise persistent university–industry collaboration on innovation?. (March 2022) - Østergaard, Christian Richter; Drejer, Ina
Abstract: This paper investigates what distinguishes persistence in relation to university–industry collaboration on innovation from the initiation and discontinuation of a collaboration. The underlying premise is that if a firm continues to collaborate with a university, it must consider that collaboration to be valuable. A quantitative analysis of over 2600 firms reveals that persistence is relatively common in university–industry collaborations on innovation, with more than a third of firms that engage in university collaboration continuing to collaborate with the same university over two consecutive periods. In addition, the analysis shows that firms' investments in collaborative capabilities and different dimensions of absorptive capacity are instrumental for persistent collaboration with a university. Furthermore, persistent collaboration with a university is strongly associated with the strategic choice to engage in sustained collaboration with a broad range of partner types. Finally, the analysis reveals that geographical proximity between a firm and a university may facilitate the initiation of a collaboration, although the nearest university is not necessarily the most suitable partner. This is illustrated by the finding that geographical proximity between a firm and a university does not matter for keeping together in a persistent collaboration. Highlights: More than a third of firms that collaborate with universities, do so persistently. Persistent collaboration applies to recurring, not alternating, university partners. Geographical proximity is not a facilitator of persistent collaboration. Collaborative capabilities depend on R&D as well as alumni-embedded social capital. Persistent collaboration is strongly associated with an open innovation process.